Rapid system prototyping with FPGAs - Cofer, R. C. (Embedded technology series., 2006)
The push to move products to market as quickly and cheaply as possible is fiercer than ever, and accordingly, engineers are always looking for new ways to provide their companies with the edge over the competition. Field-Programmable Gate Arrays (FPGAs), which are faster, denser, and more cost-effective than traditional programmable logic devices (PLDs), are quickly becoming one of the most widespread tools that embedded engineers can utilize in order to gain that needed edge. FPGAs are especially popular for prototyping designs, due to their superior speed and efficiency. This book hones in on that rapid prototyping aspect of FPGA use, showing designers exactly how they can cut time off production cycles and save their companies money drained by costly mistakes, via prototyping designs with FPGAs first. Reading it will take a designer with a basic knowledge of implementing FPGAs to the next-level of FPGA use because unlike broad beginner books on FPGAs, this book presents the required design skills in a focused, practical, example-oriented manner. *In-the-trenches expert authors assure the most applicable advice to practicing engineers *Dual focus on successfully making critical decisions and avoiding common pitfalls appeals to engineers pressured for speed and perfection *Hardware and software are both covered, in order to address the growing trend toward "cross-pollination" of engineering expertise.